Diamond-like carbon coating and surface grafting of osteoprotegerin and alendronate on polyetheretherketone to ameliorate the mechanical performance and osseointegration simultaneously. (1st May 2022) - Chen, Junfeng; Xie, Lingxia; Ruan, Qingdong; Gao, Ang; Liao, Qing; Mo, Shi; Lv, Yuanliang; Tong, Liping; Wang, Huaiyu; Chu, Paul K.; Li, Xiaoming
Abstract: Polyetheretherketone (PEEK) is an alternative to biomedical metals for fabricating bone implants, which possesses many advantages but its clinical applications are still impeded by the considerable release of worn debris and inferior osseointegration after long-term implantation. To circumvent these problems, in this study, diamond-like carbon (DLC) coating is initially fabricated on PEEK using C2 H2 + Ar plasma immersion ion implantation (PIII), and then the targeted biomolecules including osteoprotegerin (OPG) and alendronate (ALN) are simultaneously grafted onto the outer surface of DLC-coated sample by a two-step treatment consisting of N2 PIII activation and solution immersion. On one hand, DLC coating can improve the wear resistance of PEEK substrate by surface hardening. On the other hand, the introduced OPG and ALN tune the biological performances in vitro and in vivo from many aspects such as immunomodulation, anti -osteoclastogenesis and pro-osteogenesis. Collectively, our study presents a feasible one-stop solution as "deposition-activation-incubation" for the surface multi-functionalization of PEEK implants, which has a broad application prospect also due to the clean approach and excellent versatility.